Bargaining for health and safety. - Sorensen, Jeff (Columbia Journalism Review)
This article deals with the impact of the use of video display terminals (VDT) at the workplace on the health and safety of employees. Ever since VDT were introduced into offices, many employees have allegedly been suffering from tired eyes, headaches, backaches, mental stress, and other discomforts. Apparently, some unions are endorsing measures, such as rest breaks and company-paid eye examinations, aimed at protecting employees. According to Tobi Bergman, a member of the New York Committee for Occupational Safety and Health, an organization many of whose members belong to union locals, because everyone gets sore eyes sometimes, people often think of eyestrain as a minor problem, but that when it is an almost daily occurrence, eyestrain is a serious health problem, which may cause temporary deterioration of vision. Wendi Fox, who used a VDT for eight hours per day as an employee of the City of New York, reports that her screen had an orange display on a green background. In addition, the lights were very bright in the room, so there was a great deal of glare on the screen. In addition, she said that many people in her office seemed to be unusually short-tempered, adding that everybody has a headache, backaches and that there was a great deal of frustration and a lot of arguing.